Amitriptyline’s anticholinergic adverse drug reactions - a systematic multiple-indication review and meta-analysis - Brückle, Maria-Sophie; Thomas, Elizabeth T.; Seide, Svenja; Pilz, Maximilian; Gonzalez-Gonzalez, Ana I.; Dinh, Truc Sophia; Gerlach, Ferdinand M.; Harder, Sebastian; Glasziou, Paul P.; Muth, Christiane (PLOS ONE, 2023)
Background Half the US population uses drugs with anticholinergic properties. Their potential harms may outweigh their benefits. Amitriptyline is among the most frequently prescribed anticholinergic medicinal products, is used for multiple indications, and rated as strongly anticholinergic. Our objective was to explore and quantify (anticholinergic) adverse drug reactions (ADRs) in patients taking amitriptyline vs. placebo in randomized controlled trials (RCTs) involving adults and healthy individuals. Methods We searched electronic databases from their inception until 09/2022, and clinical trial registries from their inception until 09/2022. We also performed manual reference searches. Two independent reviewers selected RCTs with ≥100 participants of ≥18 years, that compared amitriptyline (taken orally) versus placebo for all indications. No language restrictions were applied. One reviewer extracted study data, ADRs, and assessed study quality, which two others verified. The primary outcome was frequency of anticholinergic ADRs as a binary outcome (absolute number of patients with/without anticholinergic ADRs) in amitriptyline vs. placebo groups. Results Twenty-three RCTs (mean dosage 5mg to 300mg amitriptyline/day) and 4217 patients (mean age 40.3 years) were included. The most frequently reported anticholinergic ADRs were dry mouth, drowsiness, somnolence, sedation, fatigue, constitutional, and unspecific anticholinergic ADRs. Random-effects meta-analyses showed anticholinergic ADRs had a higher odd’s ratio for amitriptyline versus placebo (OR = 7.41; [95% CI, 4.54 to 12.12]). Non-anticholinergic ADRs were as frequent for amitriptyline as placebo. Meta-regression analysis showed anticholinergic ADRs were not dose-dependent. Discussion The large OR in our analysis shows that ADRs indicative of anticholinergic activities can be attributed to amitriptyline. The low average age of participants in our study may limit the generalizability of the frequency of anticholinergic ADRs in older patients. A lack of dose-dependency may reflect limited reporting of the daily dosage when the ADRs occurred. The exclusion of small studies (<100 participants) decreased heterogeneity between studies, but may also have reduced our ability to detect rare events. Future studies should focus on older people, as they are more susceptible to anticholinergic ADRs. Registration PROSPERO: CRD42020111970.